Immunocytological staining reactions of anti-carcinoembryonic antigen, Ca, and anti-human milk fat globule monoclonal antibodies on benign and malignant exfoliated mesothelial cells. Issue 12 (December 1987) - Ghosh, A K; Butler, E B
Abstract : A panel of three monoclonal antibodies were used in an immunoalkaline phosphatase staining method on a series of serous effusion samples from cases of mesothelioma, lung carcinoma, and benign disease. The antibodies used were anti-carcinoembryonic (CEA) antigen, Ca, and anti-human milk fat globule membrane antigen. Antibodies to the Ca antigen and human milk fat globule membrane antigen stained 75% and 83% of mesothelioma and 75% of cases of lung carcinoma, respectively. The anti-CEA antibody stained most cases of lung carcinoma strongly but was negative on 11 of 12 cases of mesothelioma and showed weak staining on one case. Benign cases were negative with all three antibodies. These three antibodies may be useful in distinguishing benign and malignant mesothelial cells and lung carcinoma in serous effusions.